DAMPAK MAKRO EKONOMI TERHADAP INDEKS HARGA SAHAM GABUNGAN DI INDONESIA - Rutinaias Haholongan; Apry Linda Diana (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
The volatility reflected monetary situation in GDP, interest rates, and the rupiah exchange rate, can affect the economy. This shows the close effect of macroeconomics on the composite stock price index in the Indonesian capital market. This study aims to determine the effect of GDP, interest rates, exchange rates, on the joint stock price index in 2015-2019. The data analysis method of this research is multiple linear regression analysis. The results show that GDP has an effect on the joint stock price index and interest rates have a positive and significant effect on the joint stock price index. Meanwhile, the rupiah exchange rate has no effect on the joint stock price index. The results of the determination test show that the Adjusted R square adjusted is 74.3% Keyword: GDP,Exchange rate, Interest rate, IHSG